Thoracoumbilical Flap: Anatomy, Technique, and Clinical Applications in Upper Limb Reconstruction in the Era of Microvascular Surgery - Naalla, Ravikiran; De, Moumita; Dawar, Rakesh; Chauhan, Shashank; Singhal, Maneesh (Journal of Hand and Microsurgery, 2018)
Purpose Microvascular reconstruction is the standard of care for salvage of soft tissue defects in complex upper extremity due to their distinct advantages over the pedicled flaps. However, in the era of microsurgery, pedicled flaps have an acceptable significant role for reconstruction of complex soft tissue defects. The authors aim to demonstrate the versatility of pedicled thoracoumbilical flap (TUF) in selected clinical scenarios.Patients and Methods Retrospective analysis of patients who underwent TUF for upper limb posttraumatic reconstruction was performed between January 2016 and October 2017. The demographic details, etiology, wound parameters, clinical circumstances, and complications were recorded.Results Ten patients were included in the retrospective case series. Out of them, nine of the patients had critical issues, which justified a pedicled TUF over free flap. The critical issues were severe comorbid illnesses (n = 3), the paucity of recipient vessels (n = 1), salvage of hand replant and revascularization (n = 2), circumferential degloving injury to the multiple fingers and palm (n = 1), coverage for metacarpal hand (n = 1), and extensive scarring at the surgical site (n = 1). Mean age was 34.4 years (range: 11–70 years), six of them were males, and four were females. Two patients had infections resulting in wound gaping. One of the patients had flap tip necrosis.Conclusion Pedicled flaps have a significant acceptable role in this era of microsurgery, and a pedicled TUF is a versatile option for coverage of complex soft tissue defects of the forearm, wrist, hand, and fingers.Level of Evidence This is a level IV, therapeutic, and retrospective study.
Keywords: thoracoumbilical flap; pedicled flap; upper limb; paraumbilical flap